Escuela de Arte y Comunicación Visual - Hernández, Efraín (Editorial Universidad Nacional (EUNA), 2014)
This text is made up of two great nuclei of ideas. The first concerns training and historical development that allow a definition of the unique profile that the School of Art and Visual Communication offers the country through artistic education. Here we analyze the contributions of two administrative periods that are fundamental, because it is during their duration that the identity that characterizes the School as an educational and artistic institution is forged. The second part refers to the plastic-artistic, intellectual and teaching production of outstanding professors. This section characterizes the facets that distinguish the work of each author considered and gives a global idea of the values of their artistic production, their projection to the country and the artistic environment from the spheres of creation, art criticism, insertion in museums and teaching itself.